Steering Vehicle with Force-based Impedance Control for Inertia Reduction - Norsharimie, Mat Adam; Addie Irawan, Hashim (IEEE, 2018)
This paper presents the inertia control on a steering rack vehicle using interaction control approach through forcebased impedance control. Overdriven factor in a vehicle motion especially on a cornering track, is one of the issues that need to be tackled for safety and energy efficiency. Hence, in the attempt to cope with the issue, this study proposes to implement a dynamic control technique that considers the interaction between the vehicle and its terrain by using indirectly shaping inertia forces. The proposed force-based impedance control is derived by considering the forces developed by the rack steering vehicle and shaping the vehicle velocities as its kinodynamic inputs. The implementation of the proposed dynamic control, emphasis is given to the vertical and horizontal axes of the vehicle body, during which inertia could happen as its velocity is at its lowest. This proposed dynamic control strategy is verified by simulating on the steering system model with road terrain and aerodynamic frictions as disturbances. The simulation results shows that the proposed system is able to reduce the inertia forces via shaping the velocity inputs to the vehicle, even though road terrain and aerodynamic frictions are present in the cornering tracks.